2021
DOI: 10.22541/au.161846965.57392699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors affecting colistin nephrotoxicity: Advanced age and/or other factors?

Abstract: Introduction: The population is aging and older adults comprise the majority of patients in intensive care units. Colistin (COL) has been reintroduced to treat increasingly common resistant Gram-negative bacterial infections. Our study aims to investigate the factors affecting colistin nephrotoxicity in the general population and geriatric age group. Materials and Method: This retrospective study included 170 patients, 116 (68.2%) of which were in the geriatric group (age ≥65). Acute renal failure was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The sample sizes per study ranged from 11 to 4910 critically ill patients. This systematic review and meta-analysis included 3 parallel cohort studies that reported outcome measures associated with colistin and PMB use[ 62 , 76 , 80 ], 2 studies with colistin and PMB use[ 17 , 68 ], 75 studies with colistin use alone[ 16 , 18 - 40 , 42 - 57 , 59 - 61 , 64 - 67 , 70 - 75 , 78 , 81 , 83 - 99 , 101 - 102 , 104 ] and 9 studies with PMB use alone[ 41 , 58 , 63 , 69 , 77 , 79 , 82 , 100 , 103 ]. Regarding the geographical distribution, 35 studies were conducted in Europe, 31 in Asia, 6 in North America, 6 in South America and 4 in Africa.…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes per study ranged from 11 to 4910 critically ill patients. This systematic review and meta-analysis included 3 parallel cohort studies that reported outcome measures associated with colistin and PMB use[ 62 , 76 , 80 ], 2 studies with colistin and PMB use[ 17 , 68 ], 75 studies with colistin use alone[ 16 , 18 - 40 , 42 - 57 , 59 - 61 , 64 - 67 , 70 - 75 , 78 , 81 , 83 - 99 , 101 - 102 , 104 ] and 9 studies with PMB use alone[ 41 , 58 , 63 , 69 , 77 , 79 , 82 , 100 , 103 ]. Regarding the geographical distribution, 35 studies were conducted in Europe, 31 in Asia, 6 in North America, 6 in South America and 4 in Africa.…”
Section: Resultsmentioning
confidence: 99%